Pendidikan Prenatal: Perilaku Religius dan Sosial Orang Tua Lulusan Terbaik UIN Sunan Ampel Surabaya 2019-2021 - Ah Zakki Fuad; Nina Indriani; Husniyatus Salamah Zainiyati (JECED : Journal of Early Childhood Education and Development, 2023)
This study proves with scientific data the assumptions, perceptions, and myths that have developed in society which state that the religious and social behavior of parents, especially mothers who are pregnant or during the prenatal period has a significant impact on the baby to be born, both from the physical or psychological/spiritual side. This research aims to describe the religious and social behavior of parents during prenatal education. The objects and primary data of this research were the parents of students who won the best graduate title at UIN Sunan Ampel in 2019-2021 who come from different regions and socio-economic and cultural backgrounds. The research method used in this study is descriptive qualitative method, which aims to investigate the condition and behaviours of parents during the parental period. The result of this research indentified two categories of prenatal education patterns practiced by parents: 1) internalization pattern, characterized bty the belief in and engagement with religious rituals and social activities that significantly impact the unborn children; 2) integration pattern, involving the blending of sosial and religious activities by expectant parent, with the aim of ensuring that the future child aligns with their expectation. The implications of this research can serve a theoretical foundation to be emulated and applied by parents during the prenatal period.